Introduction of a new platform for parameter estimation of kinetically complex environmental systems. (December 2017) - Gharasoo, Mehdi; Thullner, Martin; Elsner, Martin
Abstract: A modeling framework (ReKinSim - Reaction Kinetics Simulator) is introduced, within which biogeochemical reactions in environmental systems can be described and inversely fitted to experimental data. Three key features of this simulation environment are: (1) a generic mathematical tool for solving sets of unlimited, arbitrary, non-linear ordinary differential equations; (2) no limitation to the number or type of reactions or other influential dynamics (e.g., isotope fractionation or small-scale mass-transfer limitations); (3) an easy to use and flexible module for nonlinear data-fitting. It allows users to easily define any kinetic model by a set of biogeochemical reactions relevant to the experimental application and to obtain the values of the kinetic parameters by fitting of the model to data. By allowing users to include the environmentally related processes and solving them along with the chemical kinetics, ReKinSim helps the user to elucidate the extent that these processes are controlled by factors other than kinetics. The novelty of the presented program primary lays in its unique combination of flexibility, computational efficiency and user-friendliness. ReKinSim's usability is showcased by four case studies of varying complexity, and compared against a set of currently available modeling tools. Highlights: Introduction of a modeling framework (ReKinSim) for solution and optimization of environmentally-related system of equations. ReKinSim's versatility allows more environmentally-related, complex dynamics to be considered in kinetic models. ReKinSim in comparison to other currently available programs is more flexible and efficient. It is easy to integrate ReKinSim with other computational environments and sources.